Ventricular fibrillation in a man shot with a Taser. Issue 8 (1st June 2010) - Naunheim, Rosanne S; Treaster, Matthew; Aubin, Chandra
Abstract : Controversy exists concerning the lethality of Tasers. These are conducted electrical weapons which incapacitate subjects by delivering an electrical charge that causes diffuse muscle contraction. In North America, over 440 deaths have been reported immediately following Taser use. Taser International has recently suggested that Tasers should not be aimed at the chest, although there is no conclusive proof that a discharge over the heart would cause an arrhythmia. The case history is presented of a young man who was shot in the chest by a Taser and presented to the emergency department in ventricular fibrillation.